GERAKAN PELESTARIAN LINGKUNGAN UNTUK GENERASI MUDA DI DESA KRUENG ALU SELASEH - Dian Erlita (Jurnal Pengabdian Pemersatu Bangsa, 2025)
This study aims to enhance environmental awareness and participation among youth through a community service program in Krueng Alu Selaseh Village. The main problem addressed is the low level of environmental awareness and limited involvement of young people in environmental conservation activities. The study employed a participatory approach consisting of preparation, implementation, and evaluation stages. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed using both qualitative and quantitative descriptive methods. The results indicate a significant improvement in knowledge, attitudes, and participation of youth in environmental conservation activities. Furthermore, the emergence of independent initiatives among participants reflects the success of the program. Supporting factors include strong collaboration with local authorities and the use of practice-based educational methods, while challenges involve limited facilities and low awareness among some community members. Therefore, this study demonstrates that a community-based participatory approach is effective in promoting youth engagement in environmental conservation.